Modeling Cell-to-Cell Spread of HIV-1 with Nonlocal Infections. (1st August 2018) - Fan, Xiaoting; Song, Yi; Zhao, Wencai
Abstract : This paper is devoted to develop a nonlocal and time-delayed reaction-diffusion model for HIV infection within host cell-to-cell viral transmissions. In a bounded spatial domain, we study threshold dynamics in terms of basic reproduction number R 0 for the heterogeneous model. Our results show that if R 0 < 1, the infection-free steady state is globally attractive, implying infection becomes extinct, while if R 0 > 1, virus will persist in the host environment.